Cerebral embolism due to left atrial myxoma in a patient presenting with chest pain and ST-segment elevation: a case report. Issue 6 (30th November 2020) - Fontes, António; Dias-Ferreira, Nuno; Tavares, Anabela; Neves, Fátima
Abstract: Background: Myocarditis is an uncommon, potentially life-threatening disease that presents with a wide range of symptoms. In acute myocarditis, chest pain (CP) may mimic typical angina and also be associated with electrocardiographic changes, including an elevation of the ST-segment. A large percentage (20–56%) of myxomas are found incidentally. Case summary: A 62-year-old female presenting with sudden onset CP and infero-lateral ST-elevation in the electrocardiogram. The diagnosis of ST-elevation myocardial infarction was presumed and administered tenecteplase. The patient was immediately transported to a percutaneous coronary intervention centre. She complained of intermittent diplopia during transport and referred constitutional symptoms for the past 2 weeks. Coronary angiography showed normal arteries. The echocardiogram revealed moderate to severe left ventricular systolic dysfunction due to large areas of akinesia sparing most of the basal segments, and a mobile mass inside the left atrium attached to the septum. The cardiac magnetic resonance (CMR) suggested the diagnosis of myocarditis with concomitant left atrial myxoma. The patient underwent resection of the myxoma. Neurological evaluation was performed due to mild vertigo while walking and diplopia in extreme eye movements. The head magnetic resonance imaging identified multiple infracentimetric lesions throughout the cerebral parenchyma compatible with an embolization process caused by fragments of the tumour. Discussion: Myocarditis can have various presentations may mimic acute myocardial infarction and CMR is critical to establish the diagnosis. Myxoma with embolic complications requires emergent surgery. To the best of our knowledge, this is the first case reported in the applicable literature of a myxoma diagnosed during a myocarditis episode.